2014
DOI: 10.1371/journal.pone.0087015
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Radiation Dependent Photoprotective Mechanism in the Diatom Pseudo-nitzschia multistriata

Abstract: Phytoplankton, such as diatoms, experience great variations of photon flux density (PFD) and light spectrum along the marine water column. Diatoms have developed some rapidly-regulated photoprotective mechanisms, such as the xanthophyll cycle activation (XC) and the non-photochemical chlorophyll fluorescence quenching (NPQ), to protect themselves from photooxidative damages caused by excess PFD. In this study, we investigate the role of blue fluence rate in combination with red radiation in shaping photoacclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 52 publications
5
74
1
Order By: Relevance
“…Fuco was the main accessory pigment, with its pool size being approximately ten- and seventeen-fold higher than that of Chl c 2 / c 3 and c 1 , respectively (Table 1). The presence of Chl c 3 , which is a pigment rarely found in diatoms, agrees with previous findings on the same species ([42] and references therein).…”
Section: Resultssupporting
confidence: 92%
“…Fuco was the main accessory pigment, with its pool size being approximately ten- and seventeen-fold higher than that of Chl c 2 / c 3 and c 1 , respectively (Table 1). The presence of Chl c 3 , which is a pigment rarely found in diatoms, agrees with previous findings on the same species ([42] and references therein).…”
Section: Resultssupporting
confidence: 92%
“…, Brunet et al. ) that chloroplast photoreceptors monitor red and blue light fluence rates in order to regulate non‐photochemical quenching quenching (NPQ) in diatoms. Energy‐dependent quenching is the major photoprotective strategy in diatoms to avoid photoinhibition, and operates on timescales of seconds to minutes (Coesel et al.…”
Section: Resultsmentioning
confidence: 99%
“…Brunet et al. () found that XC for NPQ of diatoms required red light to be initiated and a high blue fluence rate to be activated. Their results (also see Schellenberger Costa et al.…”
Section: Resultsmentioning
confidence: 99%
“…, Brunet et al . ), which would only produce 0.2–1 mg/m 3 chlorophyll for the abundances seen at PV.…”
Section: Discussionmentioning
confidence: 99%